MEDICINAL PROPERTIES OF CUMINUM CUMINUM L. AND ITS IMPORTANCE IN THE NATIONAL ECONOMY. (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
Cuminum cyminum L. is a medicinal plant, commonly known as cumin or cumin. It has long been of great importance in Eastern medicine, especially in the medicine of Central Asia, India, Iran and Arab countries. Cumin is widely used not only for its medicinal properties, but also in the food industry, perfumery and other sectors of the national economy. This article will comprehensively cover the biological and chemical composition, pharmacological effects, role in folk and modern medicine, as well as economic importance of Cuminum cyminum L.